Self‐efficacy as a mediator of the relationship between parental closeness and suicidal ideation among Malaysian adolescents - Shin, Ling Wu; Yaacob, Siti Nor (Wiley-Blackwell Publishing, 2017)
Background: Suicide has become a serious worldwide mental health problem, including Asian countries. Suicidal ideation happens prior to the actual suicidal behaviour; thus, identifying the roots of suicidal ideation is vital. This study investigated the relationships between parental closeness, self-efﬁcacy and suicidal ideation among adolescents in Malaysia. The mediation effect of self-efﬁcacy on the relationship between parental closeness and suicidal ideation was also examined. Method: A total of 684 school-going adolescents aged 14–17 years old were recruited via multistage cluster sampling. Bivariate analysis was conducted using Pearson’s correlation analysis. The mediation model was tested using SPSS macro developed by Preacher and Hayes. Results: The results showed that mother closeness, father closeness and self-efﬁcacy had signiﬁcant negative correlation with suicidal ideation. Speciﬁcally, self-efﬁcacy emerged as a partial mediator in the relation between mother closeness and suicidal ideation. Self-efﬁcacy also fully mediated the relationship between father closeness and suicidal ideation. Conclusions: The ﬁndings implied that mother closeness had stronger correlation with adolescents’ suicidal ideation compared to father closeness, while self-efﬁcacy plays an important role in the relationship between parental closeness and suicidal ideation. Prevention and intervention efforts by practitioners dealing with adolescents’ mental health issues, speciﬁcally on suicidal ideation, should seriously consider providing them with skills to enhance mother–adolescent relationship and their self-efﬁcacy.